Iptek Bagi Masyarakat: Peningkatan Motorik Anak di Perumahan Villa Kertosari Kelurahan Kertosari Kabupaten Banyuwangi - Santoso, Danang Ari; Setiabudi, Moh. Agung (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
Perumahan Villa Kertosari Kelurahan Kertosari is a new housing that was established to become a residentialarea for the community. Surely like other new housing is a problem is a public facility such as place and playground forchildren, because the housing is already inhabited by several family members. Playing infrastructure for children is veryimportant to improve the motoric (movement) of children at an early age so that the sons and daughters of familymembers housing residents do not play in the alleys of residential roads. With the help of Iptek bagi Masyarakat (IbM)program that is counseling about the development of motoric (motion) of children for the parents through workshops andprocurement of children's game equipment then the problem of motor development (movement) and activities of childrenin housing can be resolved. From the start of the playground which was originally on a residential street alley and theabsence of a play area for children in Villa Kertosari housing. Outcome targets achieved generate an understanding ofmotor development for parents and children's play areas. Given the understanding of children's motor development andchildren's play tools, parents can focus on monitoring children in one place ie in the children's play area. Until nowbeside the children housing the Villa Kertosari who play there are also children outside the scope of housing that comeinto play in the area